Recent Advances in the Siderophore Biology of Shewanella - Liu, Lulu; Wang, Wei; Wu, Shihua; Gao, Haichun (Frontiers in Microbiology, 2022)
Despite the abundance of iron in nature, iron acquisition is a challenge for life in general because the element mostly exists in the extremely insoluble ferric (Fe3+) form in oxic environments. To overcome this, microbes have evolved multiple iron uptake strategies, a common one of which is through the secretion of siderophores, which are iron-chelating metabolites generated endogenously. Siderophore-mediated iron transport, a standby when default iron transport routes are abolished under iron rich conditions, is essential under iron starvation conditions. While there has been a wealth of knowledge about the molecular basis of siderophore synthesis, uptake and regulation in model bacteria, we still know surprisingly little about siderophore biology in diverse environmental microbes. Shewanella represent a group of -proteobacteria capable of respiring a variety of organic and inorganic substrates, including iron ores. This respiratory process relies on a large number of iron proteins, c-type cytochromes in particular. Thus, iron plays an essential and special role in physiology of Shewanella. In addition, these bacteria use a single siderophore biosynthetic system to produce an array of macrocyclic dihydroxamate siderophores, some of which show particular biological activities. In this review, we first outline current understanding of siderophore synthesis, uptake and regulation in model bacteria, and subsequently discuss the siderophore biology in Shewanella.